Novel cancer therapies: treatments driven by tumour biology. Issue 1057 (15th October 2013) - Ramaswami, Ramya; Harding, Victoria; Newsom-Davis, Thomas
Abstract : The traditional view is that treatments within oncology largely consist of chemotherapy, which aims to maximise damage to the rapidly dividing cancer cells but often at the expense of normal cells and overall quality of life for the patient. The development of anticancer drugs has changed from the serendipitous discoveries of the past, to today's purposeful targeting of cancer cells which takes advantage of novel technological developments and a greater understanding of tumour biology. The aim of these new treatments is to affect the essential function of the cancer cell while sparing normal cells, and limiting side effects. The phenotypic characteristics of tumours, such as unregulated growth signalling, development of new vascular systems and the evasion of immune destruction are used to identify potential drug targets. Here we review the clinical evidence and molecular mechanisms for novel therapies that are currently in use and those that are in development.